2013
DOI: 10.1371/journal.pgen.1003815
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-Exome Sequencing Reveals a Rapid Change in the Frequency of Rare Functional Variants in a Founding Population of Humans

Abstract: Whole-exome or gene targeted resequencing in hundreds to thousands of individuals has shown that the majority of genetic variants are at low frequency in human populations. Rare variants are enriched for functional mutations and are expected to explain an important fraction of the genetic etiology of human disease, therefore having a potential medical interest. In this work, we analyze the whole-exome sequences of French-Canadian individuals, a founder population with a unique demographic history that includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
105
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 45 publications
21
105
0
Order By: Relevance
“…We have argued that other popular measures for the efficacy of selection (Lohmueller et al 2008;Casals et al 2013;Lohmueller 2014;Henn et al 2016) are biased in out-of-equilibrium populations studied over short time scales. Many previous claims that selection acted differentially in human populations (Lohmueller et al 2008;Casals et al 2013) could be explained by these biases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have argued that other popular measures for the efficacy of selection (Lohmueller et al 2008;Casals et al 2013;Lohmueller 2014;Henn et al 2016) are biased in out-of-equilibrium populations studied over short time scales. Many previous claims that selection acted differentially in human populations (Lohmueller et al 2008;Casals et al 2013) could be explained by these biases.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous claims that selection acted differentially in human populations (Lohmueller et al 2008;Casals et al 2013) could be explained by these biases. Confirming this interpretation, Fu et al (2014) found no differences in the average frequency of deleterious alleles between African Americans and European Americans in the ESP 6500 data set (NHLBI GO Exome Sequencing Project 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the GI population has likely been small and isolated for a long period of time after the OOA dispersal took place. Analyses of the GI population could therefore contribute to understanding patterns of deleterious variation and genetic load in small populations [e.g., Casals et al (2013) and Lim et al (2014)].…”
mentioning
confidence: 99%
“…[27][28][29]51 Using simulated exome data we investigated the efficacy of filtering across a wide range of methods and sequencing studies. When comparing the methods that do not leverage ancestry, we observe that the NoAncestry, FNR o5% approach leads to a slightly increased number of variants that need to be functionally followed up over the NoAncestry, f41% approach ( Table 2).…”
Section: Modeling Statistical Uncertainty Increases Filtering Efficacymentioning
confidence: 99%